The Comparison of Student Learning Outcomes Using Make a Match and Snowball Throwing Model Learning on Ecosystem Materials in Class X SMA Yayasan Perguruan Keluarga Pematangsiantar Academic Year 2019/2020 - Dian Perayanti Sinaga; Marlindoaman Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the comparison of student learning outcomes and the magnitude of differences in student learning outcomes by using the Make a Match and Snowball Throwing learning model in Ecosystem material in class X of SMA Perguruan Keluarga in the 2019/2020 Academic Year. The total population is all students of class X  are103 students, consisting of 3 classes. The sample was taken by Cluser Random Sampling, obtained 2 classes, namely the experimental class I (X MS 1) totaling 34 students and the experimental class II (X MS 2) totaling 34 students. Data analysis in this study is to look for the average value (͞x), Standard deviation (S) and hypothesis testing (t test). From the research results obtained the average value of Pre-test Experiment I and Pre-Test Experiment II were 37.79 and 42.64. The average Post-test value of experiment I and experiment II was 91.62 and 85.74 with a difference of 5.88. The standard deviation of the Pre-test and Post-test experiments I were 12.98 and 6.48, the standard deviation of the Pre-test and Post-test experiments II were 14.68 and 4.94. From the results of data analysis with the t test at a significant level α = 0.05 and the degree of freedom (dk) = 66 obtained t-count (4,208)> t-table (2.00), then Ho is rejected Ha is accepted, meaning that there are differences in student learning outcomes using make a match and snowball throwing model learning on ecosystem materials in class x SMA Yayasan Perguruan Keluarga Pematangsiantar Academic Year 2019/2020.